Racial capital and white middle class territorialization in Salvador, Brazil. Issue 2 (3rd April 2022) - Maia, Suzana; Reiter, Bernd
ABSTRACT: In this article we seek to first conceptualize whiteness as racial capital and then apply this conceptualization to analyze how whiteness functions in structuring social space in Salvador, Brazil. This article thus seeks to put into conversation different bodies of literature, namely race and racialization, critical whiteness studies, class analysis, gender analysis, and territorial analysis. In other words, we seek to provide an intersectional territorialization of how race, class, status, and gender work together to structure urban living space in general and in private, middle-class condominiums in particular. We do so by focusing on the intersection between whiteness and belonging to the middle to upper-middle classes and the mechanisms by which the approach to a white identity functions as a factor of racial capital and socioeconomic mobility.